2022
DOI: 10.1155/2022/5286921
|View full text |Cite
|
Sign up to set email alerts
|

Darcy‐Forchheimer 3D Flow of Glycerin‐Based Carbon Nanotubes on a Riga Plate with Nonlinear Thermal Radiation and Cattaneo‐Christov Heat Flux

Abstract: The current investigation deliberates the consequence of the glycerin-based carbon nanotubes with velocity slip in Darcy-Forchheimer porous medium on a convectively heated Riga plate. The Fourier heat flux theory was replaced by the Cattaneo-Christov theory. Moreover, nonlinear facets of radiation are also included in the energy expression, and this creates the energy expression which becomes highly nonlinear. The governing flow problems are altered into an ODE model with the help of suitable variables. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…e governing equations are solved analytically by applying the HAM scheme [18,[22][23][24][25][26][27][28][29][30][31][32]. In this regard, initially, we fix the initial approximation…”
Section: Homotopy Solutionsmentioning
confidence: 99%
“…e governing equations are solved analytically by applying the HAM scheme [18,[22][23][24][25][26][27][28][29][30][31][32]. In this regard, initially, we fix the initial approximation…”
Section: Homotopy Solutionsmentioning
confidence: 99%
“…They detected 3D Darcy-Forchheimer's flow of nonlinear thermal radiation. They considered water as the base fluid, and Copper and Titanium nanoliquid are considered.The thermal radiation of glycerin-based carbon nanotubes on a Riga plate over a 3D Darcy-Forchheimer was elucidated by Eswaramoorthi et al [14]. They proved that the fluid temperature increases in viscoelastic nanoliquid compared to the viscous nanofluid.…”
Section: Introductionmentioning
confidence: 99%
“…Their outcomes show that the temperature distribution escalates with the higher values of the non-linear radiation parameter. Eswaramoorthi et al [ 39 ] investigated 3D radiative flow of CNTs over a Riga plate. They concluded that the Bejan number heightens when improving the radiation parameter.…”
Section: Introductionmentioning
confidence: 99%